Mediolateral episiotomy and obstetric anal sphincter injuries in nullipara: a propensity score matching study - Or Bercovich; Daniela Chen; Bar Narkis; Anat Pardo; Eran Hadar; Asnat Walfisch; Ohad Houri (BMC Pregnancy and Childbirth)
Abstract Background Obstetric anal sphincter injuries are a notable adverse outcome of vaginal deliveries, with incidence rates ranging from 0.25% to 6%. Key risk factors for these injuries include primiparity and operative vaginal deliveries. In recent decades, the use of episiotomy as a preventive measure for obstetric anal sphincter injuries has been subject to extensive scrutiny. The objective of this study was to investigate the role of mediolateral episiotomy in preventing obstetric anal sphincter injuries during vaginal deliveries or vacuum-assisted deliveries within the context of selective use. Methods Retrospective study of all nulliparous women with a singleton gestation who underwent term vaginal delivery or vacuum-assisted delivery. A propensity score matching with a 1:1 ratio was employed to adjust for confounders. Primary outcome was obstetric anal sphincter injury rate, and the secondary outcome was a composite neonatal outcome (umbilical artery pH < 7.1, neonatal intensive care unit admission, and 5-min Apgar score < 7). Results The study cohort comprised 22,738 deliveries: 77.0% vaginal deliveries (17,518/22,738) and 23.0% vacuum-assisted deliveries (5,220/22,738) with episiotomy rates of 38.5% (6,751/17,518) and 75.8% (3,959/5,220), respectively. Separate analyses were conducted for the matched vaginal delivery group (n = 13,500) and the matched vacuum-assisted delivery group (n = 2,518). No significant differences in obstetric anal sphincter injury rates were observed in the vaginal delivery (OR 1.15, 95% CI 0.78–1.69) or vacuum-assisted delivery (OR 0.58, 95% CI 0.31–1.05) groups. However, in the vacuum-assisted delivery group, episiotomy demonstrated a borderline protective effect against obstetric anal sphincter injuries. Further adjustment for the duration of the second stage of labor duration in vacuum-assisted deliveries revealed a significant protective effect of episiotomy against obstetric anal sphincter injuries, with a number needed to treat of 28 (95% CI 15—224) in cases of prolonged second stages of labor. Episiotomy in vaginal deliveries was associated with a higher rate of composite neonatal outcome (OR 1.23, 95% CI 1.04–1.45), while vacuum-assisted deliveries showed no such association (OR 1.11, 95% CI 0.86–1.44). Conclusions In context of selective use, mediolateral episiotomy has no significant protective effect on obstetric anal sphincter injuries in women undergoing vaginal delivery. However, there is a possible benefit in vacuum-assisted delivery, especially when considering the duration of the second stage of labor.